PENERAPAN METODE DISKUSI DALAM MENINGKATKAN PENGETAHUAN GURU TENTANG PROSES PEMBELAJARAN - Aminudin Aminudin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The main task of the school supervisor is to supervise the school for which he is responsible. Supervision in this context includes monitoring, supervision, evaluation, reporting, and taking the necessary follow-up steps. This School Action Research was carried out in the fostered junior high school of Kabupaten Rokan Hilir under the supervision of the researcher. This was chosen because it supported the task of school supervisors to find out and try to improve teachers’ competence in the learning process. The stages conducted in school action research were: planning/preparing for action, implementing actions, observing and interpreting, data analysis and reflection. From the results of the study, it was known that the application of the discussion method improved teachers’ understanding in the process of learning activities. By using the discussion method, teachers’ participation become more active, meaning that it tended to be positive in following the process provided by the facilitator as well as in conducting discussions within and between groups. This success was caused by using the discussion method; teachers exchanged experiences, information with one another. In other words, discussion techniques increased cooperation between teachers through the exchange of opinions or information, so that they were more active.